Software radio development for the IEEE 802.11a/g wireless LAN - Part 1 - Erwin Kurniawan (2008)
“Delay and Correlate” algorithm is a method that can handle the CFO and timing synchronization simultaneously. This is the algorithm studied and presented in this dissertation. It correlates the received preambles with its delayed version and uses the repetitive property of the preambles. The behaviour of this algorithm, as weel as the design architecture of the synchronization module in FPGA are studied and discussed.